Effectiveness of red betel leaf extract cream for healing burn wounds - Hidayatti, Mustika; Tarigan, Setia Budi; Chiuman, Linda (Jurnal Prima Medika Sains, 2023)
Burns are a frequent type of wound that can cause complications, infection and bleeding. The use of plants and natural materials as wound-healing remedies has been known for a considerable period, although more scientific proof is required. The objective of this investigation is to examine the efficacy of red betel leaf extract ointment in curing burns on the backs of white wistar rats. The study used a pre-test post-test design with a control group. Twenty white rat samples were employed. The samples were split into four groups, consisting of five rats each. Betel leaf extract was prepared through maceration, whilst betel leaf extract cream was made using the oil-in-water emulsion method (M/A). A histopathology test was carried out to observe growth of fibroblast cells. Rat skin biopsy was taken from a 2 x 2 cm area, and data normality was tested with the Shapiro-Wilk test (p > 0.05). The One-way Anova test (p < 0.05) was used to assess the differences between the groups. To determine the most effective treatment group, a post hoc test using LSD technique was performed. The findings showed that the average percentage of burn wound healing in the control group (P0) compared to groups P1, P2, and P3 was very different.  The analysis reveals that the application of 15% betel leaf extract cream proves to be superior in treating burns in white mice in contrast to 7.5% and 10% betel leaf extract cream. At a 15% concentration, secondary metabolite compounds found in betel leaf extract are already effective in treating wounds. However, at lower concentrations they only inhibit microorganisms, making them less effective in promoting wound healing.